Acceptance of seasonal influenza vaccination among Slovenian physicians, 2016 - Učakar Veronika; Kraigher Alenka (Sciendo, 2019)
Vaccination against seasonal influenza is recommended for all healthcare workers including physicians in Slovenia to protect vulnerable individuals and reduce transmission of influenza viruses. The aim of our study is to determine the uptake of seasonal influenza vaccination among Slovenian physicians, to identify factors associated with that vaccination and assess their attitudes and beliefs regarding vaccination and vaccine-preventable diseases.